Peran Dinas Perhubungan dalam Meningkatkan Pelayanan Penerangan Jalan Umum (PJU) Kabupaten Agam - Suci Permata Sari; Boni Saputra (Policy, Law and Political Research Center, 2026)
Public street lighting (PSL) is a critical component of public services in the transportation infrastructure sector, directly impacting the safety, security, and comfort of the community. However, its implementation is often hampered by budget constraints, limited human resources, and weak maintenance and periodic monitoring mechanisms. This study aims to analyze the role of the Transportation Agency in improving public street lighting services for the community of Agam Regency and to identify the challenges faced in its implementation. The method used is a descriptive qualitative method, with data collected through in-depth interviews, observations, and documentation, involving officials from the Agam Regency Transportation Agency and residents as informants. Data analysis was conducted in three stages: data reduction, data presentation, and concluding. The research results indicate that the Transportation Agency's role has not been optimally fulfilled, as reflected in three aspects: as a motivator, facilitator, and conflict manager. Major obstacles include budget constraints resulting from the central government's efficiency measures, a lack of infrastructure, a shortage of competent human resources in electrical engineering, and the impact of weather on field operations. This study highlights the need for reforms in street lighting management through institutional capacity building, enhanced collaboration between the government and the community, and the development of technology-based monitoring systems.